2014
DOI: 10.1002/pbc.25268
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle refuelling, use of domestic wood heaters and the risk of childhood brain tumours: Results from an Australian case–control study

Abstract: Paternal refuelling of vehicles ≥4 times/month and the use of closed wood heaters before the child's birth may increase the risk of CBT. Replication in larger studies is needed. Pediatr Blood Cancer 2015;62:229-234. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
2
Order By: Relevance
“…The two case–control studies of household wood stove use and pediatric oncologic outcomes 43,49 found inconsistent associations with prenatal and postnatal wood stove use. For example, use of a wood stove (versus no use) during pregnancy was associated with higher risk of acute lymphoblastic leukemia (ALL) 43 and brain tumors 49 in childhood.…”
Section: Wood Stove Pollution and Child Health: A Narrative Review Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The two case–control studies of household wood stove use and pediatric oncologic outcomes 43,49 found inconsistent associations with prenatal and postnatal wood stove use. For example, use of a wood stove (versus no use) during pregnancy was associated with higher risk of acute lymphoblastic leukemia (ALL) 43 and brain tumors 49 in childhood.…”
Section: Wood Stove Pollution and Child Health: A Narrative Review Ofmentioning
confidence: 99%
“…For example, use of a wood stove (versus no use) during pregnancy was associated with higher risk of acute lymphoblastic leukemia (ALL) 43 and brain tumors 49 in childhood. However, frequency of wood stove use was not associated with ALL or brain tumors, and in some cases there was a paradoxical higher risk of these outcomes with “low” versus “high” wood burning frequency.…”
Section: Wood Stove Pollution and Child Health: A Narrative Review Ofmentioning
confidence: 99%
“…Результаты масштабного популяционного исследования в Техасе показали, что матери, живущие рядом с крупными дорогами или в районах с высокой плотностью проезжей части, с большей вероятностью могут иметь потомство с опухолью ЦНС, особенно эпендимомой [24]. Воздействие паров топлива и выхлопных газов при частоте заправки автомобиля будущим отцом 4 раза и более в месяц приводит к дозозависимому увеличению риска развития опухоли ЦНС у потомства [29]. Исследование методом «случай -контроль» на базе Датского канцер-регистра показало, что работа матери, связанная с выхлопными газами дизельного двигателя, ассоциирована с повышением риска возникновения у детей опухолей ЦНС (OR 1.31), особенно астроцитомы (OR 1.49) [48].…”
unclassified
“…Исследование методом «случай -контроль» на базе Датского канцер-регистра показало, что работа матери, связанная с выхлопными газами дизельного двигателя, ассоциирована с повышением риска возникновения у детей опухолей ЦНС (OR 1.31), особенно астроцитомы (OR 1.49) [48]. Имеются свидетельства об онкогенном эффекте пренатального и постнатального воздействия древесного дыма при использовании закрытых дровяных печей, приводящего к увеличению риска развития опухолей ЦНС у детей [29]. Сообщений о связи солнечной активности с опухолями ЦНС нам не встретилось.…”
unclassified
“…Smoke is an important environmental factor with proven mutagenic and genotoxic effects [15]. It has been revealed that smoking of parents before and during pregnancy can be a risk factor for the development of lymphomas and tumors of the central nervous system (CNS) in a child [16]; prenatal exposure to wood-fired smoke also increases the risk of developing CNS tumors in children [17]. Numerous studies indicate that there is a connection between childhood leukemia and the effects of tobacco smoke and exhaust gases on expectant parents before conception, and then during pregnancy and in the first years of children's life [4,8,16,18,19,20,21].…”
mentioning
confidence: 99%